Review Neu, P.; Malicky, H.; Graf, W. & Schmidt-Kloiber, A. 2018: Distribution Atlas of the European Trichoptera. - Die Tierwelt Deutschlands, 84. Teil. – ConchBooks, Harxheim: 891 pp. – ISBN: 978-3-939767-93-0. - Schmitt, Thomas (Contributions to Entomology = Beiträge zur Entomologie, 2019)
Without abstract.